Economic Growth and Crime against Small and Medium Sized Enterprises in Developing Economies - Islam, Asif (World Bank, Washington, DC, 2014)
Several studies have explored the relationship between economy-level crime rates or individual-level crime and economic growth. However, few studies have examined the relationship between economic growth and crime against firms. This study uses data for about 12,000 firms in 27 developing countries and finds that economic growth is negatively associated with crime. This relationship is stronger for small and medium firms than large firms. The study also explores several economy-wide factors and their influence on the growth-crime relationship for small and medium enterprises. The results are robust to various sensitivity checks.